Identification and antifungal sensitivity of two new species of Diaporthe isolated. Issue 2 (February 2019) - Ozawa, Kenji; Mochizuki, Kiyofumi; Takagi, Daisuke; Ishida, Kyoko; Sunada, Atsuko; Ohkusu, Kiyofumi; Kamei, Katsuhiko; Hashimoto, Akira; Tanaka, Kazuaki
Abstract: Diaporhte species are plant pathogens rarely involved in human diseases, especially eye diseases. We report our findings in two undescribed Diaporhte species. Both were identified by their morphological characteristics and by DNA sequence analyses. In Case 1, an 81-year-old male farmer who had pterygium surgery 7 years earlier developed keratitis and the causal fungus was identified as a new species of Diaporthe, D. oculi . This species can be distinguished from the closely related D. limonicola on Citrus limon (Rutaceae) by the ITS, tef1, and TUB (515/520 = 99.0% in ITS, 315/324 = 97.2% in tef1, and 601/614 = 97.9% in TUB ). The isolate from Case 2, a 68-year-old man with a rose thorn injury, was also identified as a new Diaporthe species, D. pseudooculi . Phylogenetically, D. pseudooculi is different from the closely related D. podocarpi-macrophylli by the ITS, tef1, and TUB (525/531 = 98.9% in ITS, 314/333 = 94.3% in tef1, and 436/442 = 98.6% in TUB ). We report on the identification, drug sensitivity, and treatment outcomes for these two new species of Diaporthe, D. oculi and D. pseudooculi .